Targeting MYC: Multidimensional regulation and therapeutic strategies in oncology - Yingying Duan; Zhaoshuo Liu; Qilin Wang; Junyou Zhang; Jiaxin Liu; Ziyi Zhang; Chunyan Li (Genes and Diseases)
MYC is dysregulated in approximately 70% of human cancers, strongly suggesting its essential function in cancer. MYC regulates many biological processes, such as cell cycle, metabolism, cellular senescence, apoptosis, angiogenesis, and immune escape. MYC plays a central role in carcinogenesis and is a key regulator of tumor development and drug resistance. Therefore, MYC is one of the most alluring therapeutic targets for developing cancer drugs. Although the search for direct inhibitors of MYC is challenging, MYC cannot simply be assumed to be undruggable. Targeting the MYC-MAX complex has been an effective method for directly targeting MYC. Alternatively, indirect targeting of MYC represents a more pragmatic therapeutic approach, mainly including inhibition of the transcriptional or translational processes of MYC, destabilization of the MYC protein, and blocking genes that are synthetically lethal with MYC overexpression. In this review, we delineate the multifaceted roles of MYC in cancer progression, highlighting a spectrum of therapeutic strategies and inhibitors for cancer therapy that target MYC, either directly or indirectly.